2013
DOI: 10.1073/pnas.1301126110
|View full text |Cite
|
Sign up to set email alerts
|

Visual arrestin interaction with clathrin adaptor AP-2 regulates photoreceptor survival in the vertebrate retina

Abstract: Arrestins bind ligand-activated, phosphorylated G protein-coupled receptors (GPCRs) and terminate the activation of G proteins. Additionally, nonvisual arrestin/GPCR complex can initiate G proteinindependent intracellular signals through their ability to act as scaffolds that bring other signaling molecules to the internalized GPCR. Like nonvisual arrestins, vertebrate visual arrestin (ARR1) terminates G protein signaling from light-activated, phosphorylated GPCR, rhodopsin. Unlike nonvisual arrestins, its rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

5
4

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 50 publications
(56 reference statements)
2
52
0
Order By: Relevance
“…Fixed position(s) of the C-tail in both nonvisual subtypes can promote interactions with clathrin and other partners that arrestin-1 does not bind. Interestingly, even the C-tail of arrestin-1 can interact with AP2 upon its release by receptor binding (65).…”
Section: Discussionmentioning
confidence: 99%
“…Fixed position(s) of the C-tail in both nonvisual subtypes can promote interactions with clathrin and other partners that arrestin-1 does not bind. Interestingly, even the C-tail of arrestin-1 can interact with AP2 upon its release by receptor binding (65).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore G-protein signaling is prolonged in the ARR1 or GRK1 knock-out mice, and the retina degenerates even under low ambient light (15,16). Light damage in this pathway is prevented in the transducin G t ␣ (encoded by the GNAT1 gene) knock-out background, indicating a dependence on phototransduction (8,17,18). How constitutive G-protein signaling leads to photoreceptor cell death is not well understood but is an important question to address inasmuch as defects in ARR1 and GRK1 genes occur in the human population (19,20), and certain mutations in other phototransduction genes generate "equivalent light" by driving the phototransduction cascade (21).…”
mentioning
confidence: 99%
“…Indeed, recent evidence showed that K296E recruits AP2 and other key endocytic proteins, such as endophilin and clathrin, to the outer segment (Moaven et al 2013). Interestingly, p44 rescued retinal degeneration and restored visual function to K296E mice (Moaven et al 2013). These results implicate recruitment of endocytic proteins by the K296E/arrestin-1 complex in generating the cell death signal.…”
Section: Functional Comparison Between Arrestin-1 and ß-Arrestinsmentioning
confidence: 87%
“…Given that AP2 binding alone can recruit clathrin (Laporte et al 2000), it is possible that arrestin-1 is able to recruit endocytic proteins via AP2. Indeed, recent evidence showed that K296E recruits AP2 and other key endocytic proteins, such as endophilin and clathrin, to the outer segment (Moaven et al 2013). Interestingly, p44 rescued retinal degeneration and restored visual function to K296E mice (Moaven et al 2013).…”
Section: Functional Comparison Between Arrestin-1 and ß-Arrestinsmentioning
confidence: 99%